2020
DOI: 10.5222/jaren.2020.52724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of the Physical Support to the Pregnancy on Birth Outcome

Abstract: Objectives: This study was aimed to examine the effects of physical support during the childbirth period on the birth process. Methods: Research is an experimental randomized controlled study. In the study group, each pregnant woman was directly assisted by using non-pharmacological methods without leaving the woman during her birth. Simultaneous evaluations were made to the control group with routine hospital procedures. Wijma Delivery Expectancy/ Experience Questionnaire (W-DEQ)-A was applied to all pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Studies reported that providing holistic support strategies (including uninterrupted birth support, respectful care, and good behaviors during the birth process) to the woman during childbirth can help her control her behaviors, feel good, increase self-confidence, and satisfaction rates from their birth experience and positively affect birth processes and outcomes (Bohren et al, 2016; Sydsjö et al, 2015; Weeks et al, 2017). In another study conducted in Turkey, it was reported that the women who received physical support during the birth process had higher birth satisfaction (Bayrı Bingöl et al, 2020). Our study is similar to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that providing holistic support strategies (including uninterrupted birth support, respectful care, and good behaviors during the birth process) to the woman during childbirth can help her control her behaviors, feel good, increase self-confidence, and satisfaction rates from their birth experience and positively affect birth processes and outcomes (Bohren et al, 2016; Sydsjö et al, 2015; Weeks et al, 2017). In another study conducted in Turkey, it was reported that the women who received physical support during the birth process had higher birth satisfaction (Bayrı Bingöl et al, 2020). Our study is similar to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Annelerin doğum memnuniyeti çok faktörlü olup özellikle antenatal ve innatal bakımdan etkilenmektedir (20)(21)(22). Doğuma hazırlık sınıflarının anne, bebek ve aile sağlığına dair pozitif katkılarına rağmen annelerin doğum memnuniyetine etkisine dair çalışma sonuçları çelişkilidir.…”
Section: Discussionunclassified